Students’ Self-Confident in STEAM - Irene Alcantara (Cahaya Ilmu Cendekia Publisher, 2020)
Purpose of the study: know the teacher's response about student self-confidence in STEAM. Methodology: This research uses a micro-ethnographic type case study approach. Case study research is intended to study intensively about STEAM-based physics learning and whether it has a relationship with self-confident. Main Findings: students will have good self-confidence if a teacher provides good facilities, support, and facilities. Applications of this study: very useful for teachers in implementing STEAM-based learning to improve self-confidence. Novelty/Originality of this study: This study describes the STEM-based physics learning experience by growing self-confidence.